Experimental and theoretical results of gamma shielding features for copper based shape memory alloys - Niksarlioglu, Secil; Akman, Ferdi; Agar, Osman; Kacal, Mustafa Recep; Kanca, Muhammed Sait (Pergamon-Elsevier Science Ltd, 2024)
In this study, the gamma ray attenuation characteristics for CuAlNi shape memory alloys with different proportions of Sn doping was investigated. We determined the mass attenuation coefficient (mu/rho) of CuAlNiSn alloys both experimentally and theoretically within an energy range of 59.5-1332.5 keV. The experimental measurements were made using a high purity Germanium detector (HPGe) and theoretical calculations were made using WinXCOM program. To evaluate the gamma radiation shielding abilities of the alloy samples, the obtained (mu/rho) values were used to determine the gamma protection parameters mu, HVL, TVL, MFP, and Z(eff). In addition, the radiation protection efficiency (RPE) parameter was determined using gamma ray intensities in the absence and presence of the attenuator. Further analysis of the samples was conducted using a Rigaku Miniflex 600 model computer-controlled X-ray diffractometer (CuK alpha & lambda = 1.5405 A0). The crystallographic structure of the alloys before and after irradiation was investigated. Other analysis which include EDX analysis (to investigate the chemical content) and SEM analysis (to investigate the microstructure) were conducted. According to result outcomes, gamma ray radiation did not affect the shape memory properties of structure. Another interesting observation is that, the radiation attenuation properties increase with increasing Sn concentration. Finally, we discovered that the CuAlNiSn4 alloy (which has the highest doping rate) provides good protection especially at low energy levels.
Keywords: Shape memory alloys; Mass attenuation coefficients; Effective atomic number; HPGe detector; WinXCOM software